METHODS AND TECHNIQUES FOR DEVELOPING CRITICAL THINKING WHEN STUDYING ATOMIC AND QUANTUM PHYSICS IN SECONDARY SCHOOL - Koshkar, Zhansaya; Габдуллина, Гулмира; Рыстыгулова, Венера; Битибаева, Жазира (Pedagogy and Psychology, 2023)
Due to the fact that we are now entering the era of creating a new digital society, although computer systems greatly facilitate human activities, their negative impact on algorithmic thinking has been noted. In the proposed article, new methods and techniques have been selected that contribute to the productive work of teachers in physics in order to educate a personality with flexible thinking and logical abilities, able to quickly adapt to changes and achieve their goals. In practice, when studying the section "Atomic and Quantum Physics" for 11th grade students in the secondary school-gymnasium of Konaev, the process of applying seven types of methods was considered and described: "Find a question", "Ask problematic questions", "Venn diagram", "STEM" , "Verbal Tennis", "Oriental Bazaar", "What is it?" (Drummer). The course of the lesson was focused on critical thinking, was evaluated due to the fact that each student was able to systematize his new idea and fully express his thoughts. As a result of the application, an important condition for establishing the educational process has been established, which makes it possible to form not only the main factor in the development of the cognitive interest of students, the degree of their knowledge and skills, but also important mental functions, ways of mental work.